2015
DOI: 10.2106/jbjs.n.01313
|View full text |Cite
|
Sign up to set email alerts
|

What Components Comprise the Measurement of the Tibial Tuberosity-Trochlear Groove Distance in a Patellar Dislocation Population?

Abstract: Surgical decisions of tibial tubercle transfer should be made after the careful analysis of several underlying factors of patellar dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 36 publications
7
76
3
1
Order By: Relevance
“…In the present study, LPD decreased as the TT–TG distance decreased. The decrease in LPD represents the medial shift of the patella, and the TT–TG distance represents the tibial internal rotation. The present study found a significant correlation between ΔTT–TG distance and ΔLPD, which suggests that the patellar medial–lateral displacement was affected by the tibial tubercle displacement.…”
Section: Discussionsupporting
confidence: 51%
“…In the present study, LPD decreased as the TT–TG distance decreased. The decrease in LPD represents the medial shift of the patella, and the TT–TG distance represents the tibial internal rotation. The present study found a significant correlation between ΔTT–TG distance and ΔLPD, which suggests that the patellar medial–lateral displacement was affected by the tibial tubercle displacement.…”
Section: Discussionsupporting
confidence: 51%
“…However, we found knee rotation was consistently high in Korean knees. Tensho et al30) observed a similar finding of knee rotation in Japanese knees. We believe that data from multiple centers on the normal and cut-off values may help to build a database that would serve as a guidance for better diagnosis and treatment particularly for Asian patients.…”
Section: Discussionmentioning
confidence: 61%
“…It is, however, clear that Asian knees differ from those of their Western counterpart2224). Table 6 shows the comparison of values of various parameters between the established literature based on Western population and the current study8,12,13,2530). The table further stresses the need to have a local database for diagnosis and treatment purposes as most variables are shown to differ between Asian and Western knees.…”
Section: Discussionmentioning
confidence: 75%
“…3,4 Two studies based on CT scans of subjects showed trends for the TT-TG distance to be largest for subjects with the largest tibial external rotation. 7,16 Decreased tibial external rotation for MRI scans likely contributes to up to 4 mm smaller TT-TG distance values noted for MRI scans than CT scans. [6][7][8][9] Knee coils used for MRI scans induce knee flexion, 6,17 thereby reducing tibial external rotation associated with terminal knee extension.…”
Section: Discussionmentioning
confidence: 99%